The GPI-Anchored GH76 Protein Dfg5 Affects Hyphal Morphology and Osmoregulation in the Mycoparasite Trichoderma atroviride and Is Interconnected With MAPK Signaling - Atanasova, Lea; Moreno-Ruiz, Dubraska; Grünwald-Gruber, Clemens; Hell, Viktoria; Zeilinger, Susanne (Frontiers in Microbiology, 2021)
The fungal cell wall is composed of a cross-linked matrix of chitin, glucans, mannans, galactomannans and cell wall proteins with mannan chains. Cell wall mannans are directly attached to the cell wall core, while the majority of mannoproteins is produced with a glycosylphosphatidylinositol (GPI)-anchor and then transferred to -1,6-glucan in the cell wall. In this study, we functionally characterized the transmembrane protein Dfg5 of the glycoside hydrolase family 76 (GH76) in the fungal mycoparasite Trichoderma atroviride, whose orthologue has recently been proposed to cross-link glycoproteins into the cell wall of yeast and fungi. We show that the T. atroviride Dfg5 candidate is a GPI-anchored, transmembrane, 6-hairpin member of the GH76 Dfg5 subfamily that plays an important role in hyphal morphology in this mycoparasite. Alterations in the release of proteins associated to cell wall remodeling as well as a higher amount of non-covalently bound cell surface proteins were detected in the mutants compared to the wild type. Gene expression analysis suggests that transcript levels of genes involved in glucan synthesis, of proteases involved in mycoparasitism and of the Tmk1 MAP kinase-encoding gene are influenced by Dfg5, whereas Tmk3 governs Dfg5 transcription. We show that Dfg5 controls important physiological properties of T. atroviride, such as osmotic stress resistance, hyphal morphology and cell wall stability.